Evaluation of phenolic antioxidant content in organically and conventionally grown buckwheat herb crop and its regrowth. (9th January 2017) - Žvikas, Vaidotas; Pukelevičienė, Vilma; Ivanauskas, Liudas; Romanovskaja, Danuta; Jakštas, Valdas
Abstract: BACKGROUND: Buckwheat herb is known in the pharmaceutical industry as a material rich in phenolics. Buckwheat is also capable of regrowing and producing an additional harvest in the same year. Although buckwheat herb is a popular material, it is not known whether the regrowth has features of the same quality as the first harvest. Therefore, using the herb of 15 varieties of buckwheat cultivated in Lithuania, the present study aimed to examine biometric properties, phenolic content and antioxidant activity as material quality indicators for buckwheat herb and its regrowth under organic and conventional farming conditions. RESULTS: The highest amount of rutin was indicated in the organically cultivated regrowth of 2015. Buckwheat material accumulated significantly ( P < 0.05) lower amounts of other phenolics. A significant correlation between phenolic content and antioxidant activity was observed in the herb and its regrowth in both farming systems. CONCLUSION: Regrowth was of similar quality to the first harvest in terms of phenolic content and antioxidant activity, although a downward trend in several biometric features was observed: the height of the regrowth plants was up to two‐fold smaller and biomass was five‐ to nine‐fold lower compared to that of the first harvest plants. Organic and industrial farming systems were determined to produce plants of similar quality. © 2016 Society of Chemical Industry